2001
DOI: 10.2139/ssrn.279276
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Voluntary Corporate Disclosures on the Ex ante Cost of Capital for Swiss Firms

Abstract: The relationship between disclosure quality and cost of equity capital is an important topic in today's economy. In general, economic theory and anecdotal evidence suggest a negative association. Empirical work on this link, however, is confronted with major methodological drawbacks -neither disclosure level nor cost of capital can be observed directly -and has documented somewhat confounding results so far. Adopting a finite horizon version of the residual income model, I provide evidence on the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
1
13

Year Published

2002
2002
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 43 publications
6
101
1
13
Order By: Relevance
“…Additionally, her analysis is limited to only one industry and one year. In a subsequent study, Hail (2002) also provides evidence of a negative association between disclosure quality in general and the cost of equity capital, using a sample of 73 Swiss firms. Petrova et al (2012) confirmed this notion for another sample of 121 listed Swiss firms.…”
Section: Literature Reviewmentioning
confidence: 91%
See 4 more Smart Citations
“…Additionally, her analysis is limited to only one industry and one year. In a subsequent study, Hail (2002) also provides evidence of a negative association between disclosure quality in general and the cost of equity capital, using a sample of 73 Swiss firms. Petrova et al (2012) confirmed this notion for another sample of 121 listed Swiss firms.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Disclosure theory presupposes that investors benefit from voluntary information that is provided above and beyond mandatory disclosure (Leuz and Verrecchia 2000;Hail 2002). In order to study the effect of voluntary strategy disclosure on cost of equity capital, our research is building on three related strands of literature.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations